Tauola nel libro sequente de lo infelice Guerino dito Meschino - Andrea, da Barberino, b. ca. 1370 (Incunabula. Romances ;)
Romance about Guerino, son of an Italian prince. Separated from his parents as a baby and deprived of his royal status (dubbed "Meschino," "Wretched"), he embarks on a number of chivalric adventures, travels the world, discovers his identity, and returns to recapture his kingdom. This work is also known as Guerino Meschino, Guerrino detto il Meschino and Meschino da Durazzo.